Temporal variations of depressive symptoms in patients with bipolar, borderline personality, and major depressive disorder: an ecological momentary assessment study - Martikkala, Annasofia; Baryshnikov, Ilya; Granroth-Wilding, Hanna; Heikkilä, Roope; Riihimäki, Kirsi; Saleva, Outi; Holmen, Joel; Darst, Richard; Rosenström, Tom; Aledavood, Talayeh; Isometsä, Erkki (Elsevier, 2026)
Background
Identifying the principal and comorbid diagnoses of a patient suffering from a major depressive episode (MDE) is crucial. Ecological momentary assessment (EMA) may help identify patterns of symptom fluctuations characteristic of a specific disorder and thus potentially improve the differential diagnostics.
Methods
This EMA study aimed to investigate the real-time group differences in temporal variations of depressive symptoms in patients with an ongoing MDE and a diagnosis of bipolar (BD; n = 17), borderline personality (BPD; n = 15), or major depressive disorder (MDD; n = 45) and healthy controls (HC; n = 23). Multilevel modeling analyses were performed to assess the mean level, inertia, and variability of five symptom dimensions, all ranging from positive to negative: mood, anger, anhedonia, energy, and hopelessness.
Results
All patient groups showed significantly different mean levels of all symptoms compared with HC as well as significantly greater inertia of anger and anhedonia. Furthermore, BPD patients exhibited significantly greater inertia of mood, anhedonia, and hopelessness than BD and MDD groups. By modeling different variance structures, variability of all five symptoms was found to be lowest among HC and highest among BD and/or BPD groups. Energy was the only symptom dimension where the difference in variability could also be found in the BD-BPD group comparison.
Limitations
While the overall number of participants included (n = 100) was moderate for an EMA study, numbers of patients in the BD and BPD subgroups were small.
Conclusions
These findings suggest partially different temporal variations of depressive symptoms among depressed patients with BD, BPD, or MDD and HC.